Malachite green adsorption onto Fe3O4@SiO2-NH2: isotherms, kinetic and process optimization. Issue 16 (23rd January 2015) - Sun, Ling; Hu, Shuchao; Sun, Hongmei; Guo, Huiling; Zhu, Hongda; Liu, Mingxing; Sun, Honghao
Abstract : A novel magnetic adsorbent with an amino-modified SiO2 -coated Fe3 O4 magnetite was prepared. Under the optimal conditions, the removal efficiency of malachite green is over 90% by Fe3 O4 @SiO2 -NH2 . Abstract : Higher environmental standards have made the removal of dye from water an important problem for many industrialized countries. Among the removal methods, magnetic adsorbents have received much attention for adsorption of dyes. In this paper, a novel magnetic adsorbent with an amino-modified SiO2 -coated Fe3 O4 magnetite was prepared. The analysis of Fe3 O4 @SiO2 -NH2 proved that the nanoparticles were uniform with a diameter of 90 nm. The difference between Fe3 O4 @SiO2 -NH2 and Fe3 O4 @SiO2 on the adsorption behaviour of malachite green was studied. Fe3 O4 @SiO2 -NH2 showed a good capacity for the adsorption of malachite green compared with Fe3 O4 @SiO2, which was shown to be influenced by the initial concentration and pH. Under the optimal conditions, the removal efficiency of malachite green was over 90% by Fe3 O4 @SiO2 -NH2, while using Fe3 O4 @SiO2 efficiency was below 60%. The experimental data fit well with the Freundlich isotherm and the pseudo-second-order kinetic model. In further applications, real samples were treated with Fe3 O4 @SiO2 -NH2 nanoparticles. All the results demonstrated that the Fe3 O4 @SiO2 -NH2 nanoparticles could be promising and effective adsorbents.